Some Nonlinear Elliptic Equations Have Only Constant Solutions (Journal of Partial Differential Equations, 2006)
We study some nonlinear elliptic equations on compact Riemannian manifolds. Our main concern is to find conditions which imply that such equations admit only constant solutions.
Keywords: Nonlinear elliptic equations; constant solutions